Froebel as an educator - Stewart, Mabel (My University, 1900)
Introduction: Many men are able to achieve a notoriety in their own day; but in order that their work may be truly great and enduring, it must contain an element of universality and of true worth as considered by its effect on mankind. This universality will depend upon the degree to which the work conforms to man’s elemental nature. Among those who have been able to become great in this, those have done the noblest work, who have labored for the true education of mankind. To become a great educator, a person must have a knowledge of man’s nature, a conception of the object of education, and be able to formulate a system of principles by which education may best proceed. First among such educators, we may place those who, appreciating the impressionability of the child’s nature, have recognized the importance of, and labored for the improvement of methods of early education.
Citation: Stewart, Mabel. Froebel as an educator. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Froebel; Education; Kindergarten; Theses; Manuscripts (documents)